Electrical and Magnetoresistive Properties of Ag-Co/Cu-Fe Thin Films And Bulk Rare-Earth Manganese Perovskite (Ln-Ba-Mn-O) - Abdullah, Huda (2006)
This dissertation presents the study of granular thin films of Ag-Co-Fe and Ag-Cu-Fe alloys prepared by Radio Frequency (RF) Magnetron Sputtering Technique and doped with Pr, Nd, Al, Ru and Pd on Ln-Ba-Mn-O perovskite manganates (Ln=rare-earth). The main objective is to the electrical resistance and magnetoresistance of the Ag-Co-Fe and Ag-Cu-Fe thin film and rare earth perovskite system. In order to achieve this objective, several characterizations needed to be performed, such as Scanning electron microscopy (SEM), Energy dispersive X-ray (EDX) analysis, atomic force microscope (AFM), XRay diffraction (XRD) measurement, magnetoresistance (MR) measurement and resistivity measurement. The surface morphology of thin film examined using a SEM and AFM, was found to be smooth and homogeneous. The elemental composition was determined through EDX. The optimum content of the magnetic element was about 10%,20%, 5% and 13% for AgCo2Fe2, AgCo2Fe3, AgCu2Fe2 and AgCu2Fe4 alloys, respectively. The crystal structure of the materials were analysed using a PHILIPS X-ray diffractometer. XRD diffractogram for the as-deposited films consists of (111), (200), (220) and (311) textured structure of Ag, which is dominated by (111) peak. The magnetoresistance (MR) effect was measured using a standard four-point probe technique and the measurements were performed at the room temperature and also at lower temperatures down 90 K. The lower temperatures were achieved using liquid nitrogen cryostat. Overall, MR increased with the decrease in temperature of the samples. The maximum MR value of 3.17%, 2.85% and 2.65% at 1 Tesla were obtained for the series of AgCo2Fe2 (Ts=300oC), AgCu2Fe2 (Ts=300oC) and AgCu2Fe4 (Ts=250oC), respectively which were measured at 90K. At the room temperature, the MR values for the AgCo2Fe2 and AgCu2Fe4 were higher than that of MR of AgCo2Fe3 and AgCu2Fe2 samples. The highest MR value at 1 Tesla for the annealed sample of AgCo2Fe2 (Ts=150oC) which was deposited for 120 minutes was about 3%, when the sample was annealed at 400oC for 60 minutes. The structural, electrical and magnetic properties of colossal magnetoresistance La2/3Ba1/3MnO3 and La1/2Ba1/2MnO3 doped with Pr, Nd, Al, Ru and Pd, while Pr2/3Ba1/3MnO3 was doped with Nd were also studied. Samples with various concentration of the dopant were prepared using solid state reaction method. XRD diffractogram showed a single phase pattern at low concentration with higher intensity of secondary phase at high concentration of the dopant. All samples showed the distorted orthorhombic structure. The electrical properties showed that the samples exhibited metal to insulator transition (MIT) characteristics except samples doped with Pd and Ru. Beyond specific doping level, the samples become insulator for Mn-site substitution and semiconducting behaviour for La-site substitution. This phenomenon occurred due to the smaller ionic size of dopant for La and Mn site substitution. Zener double exchange polynomial ρ = ρ0 + ρ2T2 + ρnTn, was observed well below the metalinsulator transition (Tp) temperature. Variable Range Hopping model and Adiabatic Small Polaron Hopping model well fitted at high temperature regime and values of the activation energy (Ea), density of states N(EF), Debye temperature (θD) and phonon frequency (v) could be estimated. It showed that Ea for all samples were within the range of ~30 meV to ~180 meV. Magnetoresistance measurement showed that MR ratio increased when decrease in temperature and and increase in dopant concentration. The maximum values of MR at La-site substitution was higher than at Ba-site and Mn-site substitutions. The highest MR value was 63.491% for sample (La1-xNdx)1/2Ba1/2MnO3 (x=1) measured for 150 K at 1 Tesla. All samples exhibit low-field magnetoresistance (LFMR) and high-field magnetoresistance (HFMR) regions except (La1- xNdx)1/2Ba1/2MnO3 samples. The LFMR ratio reduced with increasing temperature. The SEM micrographs indicated the grains sizes were reduced and level of porosity increased as the dopant content increased which can be seen in all samples except La2/3(Ba1- xPdx)1/3MnO3.